The Process of Developing Gelatinization and Saccharification with Variations in Temperature and Period of Glucose Sago Material - Megavitry, Rissa; Nurhijrah, Nurhijrah (International Journal of Environment, Engineering & Education, 2019)
Initial temperature variations carried out for the gelatinization stage and sampling every six hours during the saccharification process, which lasted 72 hours. The liquefaction process using the Î±-amylase enzyme and then proceeds to the saccharification process with the glucoamylase enzyme. The raw material used is sago flour, which has relatively high starch content. The method in this research 1) Sample preparation; 2) Gelatinization Process; 3) Liquefaction Process; 4) Saccharification Process; 5) Reducing Sugar Analysis; 6) Sweetness Level Analysis; 7) Dextrose Equivalent Analysis; 8) Statistical Analysis. The result for analysis obtained the average value of reducing sugar at the use of 121 degrees Celsius gelatinization temperature is 108.33 g/L higher than the value of reducing sugar at the use of 87 degrees Celsius gelatinization temperature is 94.56 g/L. The analysis obtained the average value of sweetness level at the use of 121 degrees Celsius gelatinization temperature is 23.22 degrees Brix higher than the value of sweetness level at the use of 87 degrees Celsius gelatinization temperature is 20.82 degrees Brix. The analysis obtained the average value of dextrose equivalent at the use of 121 degrees Celsius gelatinization temperature is 54,17 percent higher than the value of dextrose equivalent at the use of 87 degrees Celsius gelatinization temperature is 47.28 percent. The high potential of glucose syrup made from sago expected to motivate the development of home industries that use glucose syrup in various food productions.